2020
DOI: 10.1101/2020.01.20.912592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamate dehydrogenase (Gdh2)-dependent alkalization is dispensable for escape from macrophages and virulence ofCandida albicans

Abstract: 31Candida albicans cells depend on the energy derived from amino acid catabolism to 32 induce and sustain hyphal growth inside phagosomes of engulfing macrophages. 33The concomitant deamination of amino acids is thought to neutralize the acidic 34 microenvironment of phagosomes, a presumed requisite for survival and initiation of 35 hyphal growth. Here, in contrast to an existing model, we show that mitochondrial-36 localized NAD + -dependent glutamate dehydrogenase (GDH2) catalyzing the 37 deamination of glut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…S1A) [14]; we designate stp2-/-/-as stp2. As in previous reports, the stp2 strain showed a clear defect in Silao et al, 2023 Gdh2 functions as a rheostat controlling extracellular pH alkalization even at high density (OD  5) (Fig. 4A, upper panel).…”
Section: Stp2 and Put3 Are Key Regulators Of Gdh2 Put1 And Put2 Expre...supporting
confidence: 86%
See 3 more Smart Citations
“…S1A) [14]; we designate stp2-/-/-as stp2. As in previous reports, the stp2 strain showed a clear defect in Silao et al, 2023 Gdh2 functions as a rheostat controlling extracellular pH alkalization even at high density (OD  5) (Fig. 4A, upper panel).…”
Section: Stp2 and Put3 Are Key Regulators Of Gdh2 Put1 And Put2 Expre...supporting
confidence: 86%
“…The copyright holder for this preprint this version posted August 4, 2023. ; https://doi.org/10.1101/2023.08.04.551922 doi: bioRxiv preprint Silao et al, 2023 Gdh2 functions as a rheostat controlling extracellular pH Silao et al, 2023 Gdh2 functions as a rheostat controlling extracellular pH normally thrives in the acidic vaginal microenvironment, we found that environmental alkalization does not directly limit the growth of this competing microorganism.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A third, NAD-dependent GDH (GDH2) localized in the mitochondria degrades glutamate to α-ketoglutarate and ammonia and thus contributes to anaplerosis of Krebs cycle. Glutamate and glutamine contribute for 85% and 15% of total cellular nitrogen, respectively in S. cerevisiae (Miller and Magasanik, 1990) (Mara et al, 2018) (https://www.yeastgenome.org/locus/S000002374#protein) (Silao et al, 2020). In addition to being a nitrogen donor, Glutamate is also utilized as the sole source of carbon by Pichia pastoris ( a.k.a.…”
Section: Introductionmentioning
confidence: 99%